Integrated Curriculum in Nepal: Opportunities, Challenges, and Future Directions - KC, Sher Bahadur (Journal of Musikot Campus, 2025)
This study explores the concept and implementation of integrated curriculum design, with a specific focus on Nepal’s basic education system. Drawing upon global models of curriculum integration—ranging from disciplinary to transdisciplinary approaches—it examines how interdisciplinary methods enhance real-world learning, critical thinking, and 21st-century competencies. Using a qualitative document analysis approach, the research investigates national curriculum policies, including the National Curriculum Framework 2019 and the integrated curriculum implemented in Grades 1–3 in Nepal. The findings highlight the potential of integrated curriculum to improve student engagement, foster meaningful connections across subjects, and support holistic development. However, challenges persist, such as insufficient teacher preparation, limited higher-order cognitive engagement, and inequitable distribution of content. The study concludes that effective integration requires robust teacher training, flexible curriculum design, and a shift from teacher-cantered practices to learner-cantered methodologies. Recommendations are provided for policymakers and educators to address these gaps and to promote an educational environment that supports innovation, relevance, and student empowerment.